Immunological Defence beyond Vaccination- A Review - Ping-Chung Leung; Chung-lap Ben Chan; Chun-kwok Wong (Journal of Vaccines and Immunology - Peertechz Publications, 2020)
The Pandemic has been with us in the whole world for over half a year. There seems no signs of slowing down. Traditionally, infection problems are dealt with by experts and scholars who clarify the cause of the disease and the pathological involvements; work out the effective treatment protocol, then organize a public health program for prevention. Unfortunately, with regard to this current devastating pandemic, up to today there is yet no consensus on the use of therapy: anti-flu, anti HIV, antimalarials and steroidal classics have all been tried. New drugs, of course, has been on the list.